2021
DOI: 10.1007/s12601-021-00041-z
|View full text |Cite
|
Sign up to set email alerts
|

Age and Growth of Southern Bluefin Tuna, Thunnus maccoyii, Based on Otolith Microstructure

Abstract: Age and growth of southern bluefin tuna (SBT, Thunnus maccoyii) were estimated based on otoliths collected by Korean tuna longline vessels in the Atlantic and Indian Oceans from 2015 to 2019. A total of 739 specimens were used to estimate age and growth of SBT, with sizes ranging from 66 to 181 cm in fork length. It was confirmed that the otolith is a suitable aging characteristic for determining SBT age, and otolith annuli can be used as an annual ring. The relationship between fork length (FL) and total weig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…According to the L ∞ and K obtained in this study, BET was categorized as slow growth and long-lived species. As required, the BET has a K value lesser than 1.0 year -1 (Sparre and Venema 1998) thus, it has similar characteristics among tunas (Farley et al 2013;Gunn et al 2008;Ku et al 2021). We also compared the BET growth parameters with those of previous studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the L ∞ and K obtained in this study, BET was categorized as slow growth and long-lived species. As required, the BET has a K value lesser than 1.0 year -1 (Sparre and Venema 1998) thus, it has similar characteristics among tunas (Farley et al 2013;Gunn et al 2008;Ku et al 2021). We also compared the BET growth parameters with those of previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding accurate stock assessment, age-based growth modeling is substantial for estimating catch age structure, mortality, longevity, and age at maturity (Eveson et al 2015;Farley et al 2006;Sardenne et al 2015). Numerous studies have concluded that counts of growth microstructures in sagittal otoliths can provide reliable age and growth estimation of tunas (Farley et al 2006;Gunn et al 2008;Ku et al 2021). Otoliths are constituted primarily of calcium carbonate (CaCO 3 ) and a small quantity of organic matrix, which are deposited as daily and annual increments.…”
Section: Introductionmentioning
confidence: 99%
“…Here, an otolith-based aging approach was used to characterize age, growth, and mortality relationships for Blackfin Tuna in the northern GOM. Otolith-based aging methods have been used to develop growth curves for several tunas (Murua et al 2017), including Atlantic Bluefin Tuna (Restrepo et al 2010), Southern Bluefin Tuna (Ku et al 2021), Yellowfin Tuna (Pacicco et al 2021), and Albacore (Wells et al 2013). While daily increment formation has been examined for Blackfin Tuna (Doray et al 2004), otolith-based estimates of age and growth are limited throughout their range.…”
Section: Introductionmentioning
confidence: 99%
“…2010), Southern Bluefin Tuna (Ku et al. 2021), Yellowfin Tuna (Pacicco et al. 2021), and Albacore (Wells et al.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies present only preliminary results, indicating that the estimated growth rate of these species is uncertain and is not definitively linked to the aging of tuna. Ku et al (2021) investigated the age and growth patterns of the Southern Bluefin Tuna (Thunnus maccoyii) by analyzing the microstructure of its otoliths. Similarly, the FAO released a preliminary study on determining the age of Bluefin Tuna (Thunnus thynnus), while another study has provided a more recent estimation of the growth pattern of Western Atlantic Bluefin Tuna (Restrepo et al 2010).…”
Section: Introductionmentioning
confidence: 99%